The process capability of HAL - Fellman, Jack (Printed Circuit Fabrication, 1999)
The Hot Air Leveling Users Group (HUG) is a non-profit organization comprised of PCB manufacturers, designers, assemblers, chemical and equipment suppliers whose charter is to understand the complexities of the hot air leveling (HAL) manufacturing process as it relates to the contract assembler. A test vehicle was designed by the HUG team and manufactured by member companies. A preliminary report on data from one HAL process is presented.